A Case of Primary Ovarian Lymphoma Presenting as a Rectal Submucosal Tumor - Jung, Il Soon (The Korean Society of Coloproctology, 2012)
Primary ovarian lymphoma is a rare malignancy whose symptoms or signs are usually nonspecific. In this article, we report a very rare case initially presenting as a rectal submucosal-tumor-like lesion with a defecation disturbance caused by primary ovarian lymphoma with bilateral involvement. A 42-year-old woman visited chungnam national university hospital complaining of persistent defecation disturbance for 6 months. Colonoscopy demonstrated compression of the rectum by an extrinsic mass mimicking a rectal submucosal tumor. Magnetic resonance imaging detected bilateral ovarian tumors, 9.3 cm and 5.4 cm each in diameter, compressing the rectum without enlarged lymph nodes. The diagnosis was established following a bilateral adnexectomy and histological studies of the excised tissue. The tumor was classified as a diffuse large B-cell lymphoma. The patient was prescribed six cycles of standard CHOP (cyclophosphamide, hydroxydaunorubicin, vincristine, prednisolone) regimen and is presently on treatment.